PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI PERDAGANGAN ELEKTRONIK DI INDONESIA - Jannah, Annisa Fitratul; Yamani, M; Barus, Sonia Ivana (Jurnal Hukum Ius Publicum, 2025)
The development of information technology has accelerated the growth of electronic commerce (e-commerce) transactions in Indonesia, which provides convenience for consumers but also increases the risk of violations of their rights. This research aims to analyze the legal protection available to consumers in the context of e-commerce, highlighting existing regulations and challenges in their implementation. The method used in this research is a normative juridical approach, which issued Law Number 8 of 1999 concerning Consumer Protection (UUPK) and Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) as the main legal framework. Even though there are regulations governing consumer protection, there are still several limitations, such as the definition of business actors which only applies in the territory of Indonesia and guarantees of effective settlement. Apart from that, transaction security issues and consumers' low understanding of their rights are also obstacles. This research aims to provide recommendations to strengthen legal protection for consumers, so as to create a safer and more reliable e-commerce ecosystem.